"This is My Girl": How Men's Desires Obscure Women's Sexual Aggression Experiences in Public Drinking Settings. (February 2021) - Becker, Sarah; Tinkler, Justine E.
In this article, we use 198 interviews with young men and women to explore how they define and negotiate boundaries of unwanted sexual contact in public drinking settings. Men and women's contrasting experiences reveal that in bars and nightclubs, sexual aggression against women is routine and typically involves physical threat. For men, however, consensual and nonaggressive contact can register as problematic when disruptive to men's control of heterosexual interactions. Men's aggression toward other men who disrupt their access to women is cause and consequence of women's sexual aggression experiences being less visible. We contribute to sexual assault literature by illustrating how heterosexual power dynamics—specifically, disproportionate visibility and defense of men's desires—shape tolerance of barroom sexual aggression, discourage bystander intervention, and set the stage for more serious forms of assault to occur and go unpunished.